A new type of ultrasonic water alleviates constipation with favorable safety - Hu, Jiarong; Hu, Xinyi; Huang, Wenjie; Wang, Fen; Xia, Zhongqi; Zhu, Chenyang; Chow, Junwei; Yan, Shiwei; Li, Longzhou; Liu, Haiyang; Cui, Shufen; Ma, Guo (Frontiers in Toxicology, 2025)
IntroductionUltrasonic water (UW) is a novel category of functional drinking water. This study aimed to investigate its laxative efficacy and underlying mechanisms using a constipation model in SD rats, while also conducting a comprehensive safety evaluation.MethodsA rat constipation model was established to assess the purgative effect of UW. Safety was systematically evaluated through acute oral toxicity tests, subacute oral toxicity tests, a bone marrow cell micronucleus test, and an Ames test. Serum levels of gastrointestinal hormones—including motilin, substance P, vasoactive intestinal peptide, acetylcholinesterase, and somatostatin—were measured to explore potential mechanisms.Results and discussionUW significantly improved constipation symptoms of the test SD rats, with a significant increase in body weight (16.03 ± 5.32%) compared to the model group (8.67 ± 4.02%, P < 0.05). Compared to the model group, serum levels of excitatory gastrointestinal hormones were significantly elevated 4.20% (motilin), 10.87% (substance P), 36.69% (vasoactive intestinal peptide) and 12.89% (acetylcholinesterase) (P < 0.05), while somatostatin, was markedly reduced 22.40% (P < 0.05), respectively. Acute oral LD50 values of UW were higher than 20000 mg/kg, indicating practical non-toxicity. In the subacute toxicity test, compared to those in the control group, performances, blood routine indexes and serum biochemical indexes of the rats in the UW group showed no statistical difference (P > 0.05), and all the organs and tissues of the rats in both groups maintained normal morphology. Micronucleus effect of UW was not found when the dosage of UW was up to 20000 mg/kg. UW also showed no mutagenic activity on standard test strains. In summary, UW exhibited favorable purgative effect and safety.